Application of an unstructured overset method for predicting the gear windage power losses - Y. Dai; L. Xu; X. Zhu; B. Ouyang (Engineering Applications of Computational Fluid Mechanics, 2021)
Enhancing the efficiency of gear systems is of significance to reduce fuel consumption and overall weight. Windage power losses become prevailing in high-speed gear systems, such as aero-engine applications. To avoid the shortages and limitations of commonly used methods (e.g. negative volume in dynamic mesh method and one moving object in sliding meshing method), this paper describes an unstructured overset computational fluid dynamics technology to simulate the airflow pattern in a gearbox and calculate the windage losses. A disk, a spur gear and a helical gear, spinning in the air at rotational speed up to 7200 r/min are studied respectively, the windage power losses obtained by the numerical method show good agreement with experimental data and analytical findings in the open literature. Meanwhile, the associated deceleration torques exerted by pressure and viscous forces on spinning gear surfaces are also determined. Furthermore, the overset method facilitates to estimate the windage losses of a non-meshing gear pair. The results of this paper indicate that the overset method can accurately predict the windage power losses and provide a new route to investigate the flow pattern surrounding the gears. This method can serve as an effective tool for engineering applications in the future.